Teacher's Speech Act in Classroom Learning Process at SMA Negeri 2 Poso - Toedje, Charles Setiawan (Sintuwu Maroso Journal of English Teaching, 2024)
: This study aims to find out the teacher’s speech act during the learning process that is taking places in class X of SMA Negeri 2 Poso. This research uses descriptive qualitative as the research design and use the theory of Speech Act by Searle (1979). The subject of the research is an English teacher at SMA Negeri 2 Poso. The data are collected through field notes, recording, and interview instruments during teaching-learning process at the classroom. The result of the research shows that from 34 data of the teacher’s utterances, there are four types of speech act based on Searle’s theory, for instance, 27 utterances of directive speech act, 6 utterances of Assertive speech act, 4 utterances of Expressive speech act, and 3 utterances of Declarative speech act.